Pola sebaran kelompok telur Ostrinia furnacalis Guenée (Lepidoptera: Crambidae) pada lahan jagung - da-Lopez, Yosefus F.; Trisyono, Y. Andi; Witjaksono, Witjaksono; Subiadi, Subiadi (Jurnal Entomologi Indonesia, 2014)
Asian corn borer, Ostrinia furnacalis Guenée, is known as an important pest of maize, Zea mays L., in both whorl and reproductive stages. Management decisions based on egg-mass density is useful because decision is made before damage occurs. Observation on O. furnacalis egg-mass distribution in maize-field was carried out in Agricultural Training, Research, and Development Station (ATRD) UGM, Yogyakarta. The number of egg-masses laid on each plant surface in maize-field was sampled in reproductive stage of corn at 52 – 58 days after planting. The spatial dispersion was analyzed using the ratio variance-to-mean (Ïƒ2/Î¼ = IÎ´), Morista's Index (IÎ³), and the negative binomial parameter (Îº-value). The results showed that horizontal and vertical distributions were aggregated distributions (Ïƒ2 > Î¼ or Ïƒ2/Î¼ > 1). In line with the increasing age of plant, the degree of clustering or aggregation likely tended to decline (the Îº-value increased, Morisita index decreased) indicating the possible departure from aggregation to randomness (Poison distribution) due to the heterogeneity of the environment, such as microclimate, preferred parts of the plants, and occurrence of natural enemies. The results concluded that the horizontal and vertical distributions of egg-masses of O. furnacalis on corn in generative phase were clustered with the degree of clustering tended to decrease by the increase of age of corn. These findings provide the bases for further study on the ecology and biology of O. furnacalis for management decision-making process.